Degradation tolerant optimal control design for stochastic linear systems - Kanso, Soha; Jha, Mayank Shekhar; Theilliol, Didier (Zielona Góra: Uniwersytet Zielonogórski)
Safety-critical and mission-critical systems are often sensitive to functional degradation at the system or component level. Such degradation dynamics are often dependent on system usage (or control input), and may lead to significant losses and a potential system failure. Therefore, it becomes imperative to develop control designs that are able to ensure system stability and performance whilst mitigating the effects of incipient degradation by modulating the control input appropriately.
Keywords: linear quadratic Gaussian control; optimal control; Kalman filters; stochastic linear system; degradation